Practical Apects of Determining The Rent Amount for The Lease of Agricultural Land: Case Study Calarasi County - Emil MUSAT; Rares-Alexandru IONESCU (Communications of International Proceedings, 2021)
Knowing how to determine the value of the rent of agricultural land and the elements underlying its establishment, is useful for understanding the operation mechanism of the land lease market, especially regarding the sizing demand. Considering that 61.27% of the Used Agricultural Area in Calarasi County is owned and leased, compared to only 28.65% nationally, it results that, by the size of the phenomenon of leasing agricultural land in this county , we can consider that the practices used by agricultural exploitations in Calarasi County can be considered landmarks for managing leases and attracting new areas of agricultural land in order to increase the exploitation size. In order to identify the concrete way in which the contract value of the agricultural land lease is established, the practices used at four agricultural exploitations in Calarasi County, representative in terms of size, location and facilities, were researched. The legislation in force leaves the parties free to determine the actual value of the leases. In the researched area, the most important criterion used to determine the value of the lease is the size of the agricultural land covered by the contract.
Keywords: Agricultural Land Lease; The Rent Amount; Criterion.